2003
DOI: 10.1159/000067739
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Enhancement of Bupivacaine Anesthesia in Mice by Drugs That Open Sodium Channels

Abstract: Sodium channel drugs were used to modulate the anesthetic effects of bupivacaine in mice. Anesthesia was measured following perisciatic injection of bupivacaine with vehicle or neurotoxin in the popliteal region. The site 1 Na+ channel blocker tetrodotoxin alone was inactive, but increased the anesthetic effects of bupivacaine. We hypothesized that the site 2 and site 3 Na+ channel openers veratridine and anemone toxin II (ATXII), respectively, would antagonize bupivacaine. Paradoxically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…We have previously demonstrated that drugs that alter calcium channels or calcium release from intracellular pools can also change the potency of bupivacaine in a several tests of radiant heat nociception Smith and Lindsay, 2003;Smith et al, 2004). We have previously demonstrated that drugs that alter calcium channels or calcium release from intracellular pools can also change the potency of bupivacaine in a several tests of radiant heat nociception Smith and Lindsay, 2003;Smith et al, 2004).…”
Section: Influence Of Ibutilide On Bupivacaine In the Popliteal Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that drugs that alter calcium channels or calcium release from intracellular pools can also change the potency of bupivacaine in a several tests of radiant heat nociception Smith and Lindsay, 2003;Smith et al, 2004). We have previously demonstrated that drugs that alter calcium channels or calcium release from intracellular pools can also change the potency of bupivacaine in a several tests of radiant heat nociception Smith and Lindsay, 2003;Smith et al, 2004).…”
Section: Influence Of Ibutilide On Bupivacaine In the Popliteal Regionmentioning
confidence: 99%
“…To our knowledge, this is the first study to determine the influence of ibutilide alone and co-administered with bupivacaine in a test of nociception. We have previously demonstrated that drugs that alter calcium channels or calcium release from intracellular pools can also change the potency of bupivacaine in a several tests of radiant heat nociception Smith and Lindsay, 2003;Smith et al, 2004). Within the popliteal region, the sensory and motor axons of the sciatic nerve bifurcate into the common fibular nerve and the tibial branch which innervate the lower leg and paw.…”
Section: Influence Of Ibutilide On Bupivacaine In the Popliteal Regionmentioning
confidence: 99%